Heat Transfer Analysis of Enhanced Geothermal System Based on Heat-Fluid-Structure Coupling Model - Linchao Wang; Xin Liang; Xuyang Shi; Jianyong Han; Yang Chen; Wan Zhang (Geofluids, 2023)
Dry hot rock geothermal resources by virtue of its wide distribution, large reserves, clean and low-carbon, stable, high utilization rate, and other characteristics have been widely used. The enhanced geothermal system (EGS) is the most efficient approach for harnessing and exploiting geothermal energy from hot, arid rock formations. To investigate the impact of varying parameters on heat recovery in EGS operations, we employed the COMSOL numerical simulation software to construct a seepage heat transfer model for fractured rock masses. Essential parameters and boundary conditions were established, followed by conducting numerical simulations. Through the numerical simulation results, the temporal and spatial changes of coupling effects among seepage field, stress field, and temperature field in fractured rock mass were analyzed. We investigated the impact of water injection temperature, injection-production pressure difference, injection flow rate, and initial reservoir temperature on the heat transfer process. The findings indicate that raising the water injection temperature and injection-production pressure difference can enhance the reservoir’s heat recovery capability. However, it may also accelerate thermal breakthrough and reduce the system’s operational lifespan. The higher injection flow rate can improve the heat recovery efficiency. However, too large injection flow can cause problems in other aspects of the reservoir; increasing reservoir temperature leads to higher production temperatures, which can potentially result in dynamic catastrophes. Therefore, while ensuring the heat recovery efficiency of the system, the operation life of the system can be extended by adjusting the water injection temperature in stages, setting a reasonable injection and production pressure difference, and selecting an appropriate injection flow rate, so as to achieve the purpose of EGS optimization.